DChIPRep, an R/Bioconductor package for differential enrichment analysis in chromatin studies - Chabbert,Christophe D; Steinmetz,Lars M; Klaus,Bernd (PeerJ PrePrints, 2016)
The genome–wide study of epigenetic states requires the integrative analysis of histone modification ChIP–seq data. Here, we introduce an easy–to–use analytic framework to compare profiles of enrichment in histone modifications around classes of genomic elements, e.g. transcription start sites (TSS). Our framework is available via the user–friendly R/Bioconductor package DChIPRep. DChIPRep uses biological replicate information as well as chromatin Input data to allow for a rigorous assessment of differential enrichment. DChIPRep is available for download through the Bioconductor project at http://bioconductor.org/packages/DChIPRep. Contact DChIPRep@gmail.com
Keywords: Bioinformatics; Computational Biology; Genomics; ChiP–Seq; Chromatin; Histone–Modifications; Differential Enrichment; Statistics